Alternative Shuar Mining from the Grassroots: The Kenkuim Case in the Ecuadorian Amazon - Lembke, Magnus; Wajari, Alipio; Vera Vera, Ana Karina; Juank Chuint, Fausto; Ankuash Quizhpe, Blanca Silvia (Whispers from below: Community-based tourism and (other) Ecuadorian initiatives for alternative economies: A closer look, 2026)
This study examines artisanal gold mining in Kenkuim as a form of alternative economy and resistance. Through the community-based enterprise Exploken, the local population challenges the transnational extractivist model by adopting a socio-ecologically responsible approach. Self-management of resources enables the funding of health and education, transforming a contentious activity into a tool for economic sovereignty and the defense of the Amazon’s ancestral heritage.